THE FLEXIBILITY OF CURRICULUM FOR PERSONALISED LEARNING - Kaminskiene, Lina; DeUrraza, Maria Jose (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The paper discusses two main approaches to personalised learning through humanistic and functionalist approaches and tries to identify the shared areas. The paper argues that these areas are related to the development of a flexible curriculum and are focused on learner's needs and potentials, learner's ownership of the learning process, recognition of learner’s pace and assessing personal progress. The paper is based on literature review, trying to systemise current theoretical and practical approaches to personalised learning.